Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Dedekind modular law. If $A,B,C$ are subgroups of a group $G$ with $A \subseteq B$ then $A(B \cap C) = B \cap AC$.

Below is what I want to prove. Let K be a finite group with $K = LH$, where $L,H$ are subgroups of $K$ with relatively prime orders. If $U$ is a maximal subgroup of $L$ then $UH = HU$. Proof:

$HU = HU \cap LH = (HU \cap L)H = (H \cap L)UH = UH$

Is my proof true?

share|improve this question
    
I edited your question but your should really take the time to learn how to properly write the mathematical symbols that you want to use. It's basically a matter of inserting some "$" signs here and there and it really improves the legibility of your post. –  Adrián Barquero Apr 14 '12 at 18:34
    
I will try to learn. –  user28083 Apr 14 '12 at 19:18
    
How did you get $HU\cap LH = (HU\cap L)H$? –  anon Apr 14 '12 at 20:03
    
I put $A=H$, $B=HU$, $C=L$ and used the law in the following form $B \cap CA=(B \cap C)A$ –  user28083 Apr 14 '12 at 20:10
    
Thank you very much, I did not know that I was assuming $UH$ is a group already in my proof. –  user28083 Apr 18 '12 at 14:29

1 Answer 1

There is a mistake in your proof. When you state Dedekind's rule above, you assume $A, B, C$ are subgroups of a group. So, to get your second equality using Dedekind's rule you assume $B= HU$ is a group, but that's what you are trying to prove. (Recall, $UH = HU$ if and only if $UH$ is a group.)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.